Characterization of the limited specificity of antigen recognition in earthworms - Köhlerová, P; Tucková, L; Bilej, M (Folia microbiologica, 1999)
Parenteral administration of foreign proteins results in earthworms in significantly increased levels of the antigen-binding protein (ABP). The earthworms (Lumbricus terrestris and Eisenia foetida; Oligochaeta, Annelida) were stimulated with different proteins and the ABP response was followed with an anti-ABP monoclonal antibody and in ligand assay with biotin conjugates of all proteins used for stimulation. ABP levels are increased after the stimulation with different proteins irrespective of the size and extent of glycosylation. Molar mass of the ABP molecules was always the same, 56 kDa in L. terrestris and 60 kDa in E. foetida. The level of the specificity is considerably lower in comparison with immunoglobulins since ABP reacts not only with the protein used for stimulation but also, though to lesser extent, with related proteins.
Keywords: Protein Binding; Proteins; monoklonální protilátky; Antibodies, Monoclonal; antigeny heterofilní; Animals; antigeny; Antigens; Antigens, Heterophile; proteiny; zvířata; Oligochaeta; vazba proteinů